(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: Our basic motivation was to classify the graffiti that appearing in our psychiatric ward. We matched the manifestations previously identified in prisons with the data collected in the psychiatric ward according to content and symbolic criteria. We also aimed to uncover evidence of intersections between psychopathological and criminological developmental pathways. Methodology: In our research, we compared symbol systems transmitted by hundreds of graffiti from prisons and psychiatric wards. As a first step, we classified the psychiatric ward graffiti according to their content, and then attempted to find a counterpart of these symbols in prison graffiti. At one point we also analysed the graffiti material: in both places we found graffiti written in blood. Findings: Out of a total of 18 motifs identified, only one was not found in prisons. This was the sign for a call for help. The clear difference between the two types of graffiti was the stronger tendency for symbolism among adolescents with psychiatric disorders. This may mean that repressed impulsivity in adolescents more easily becomes a condensed symbol that substitutes for cognitive content and the underlying higher activation level. Value: We are by no means claiming that all children admitted to psychiatric wards deviate or become delinquent, but we do not exclude the p ossibility, nor do we see the experience of confinement as being entirely the same. Our results shed light on the fact that deviance processes can be interpreted from both a psychopathological and a criminological perspective. We have shown why wall scribbles left in psychiatric wards can be harmful, but we have also indicated what information can be extracted from them.